Antibacterial Property of Extract of Erveniastrum nepalense (Edible Lichen) Collected from Hilly Regions of Eastern Nepal (Tribhuvan University Journal of Microbiology, 2019)
Objectives: To evaluate the antibacterial property of Everniastrum nepalense(edible lichen)collected from eastern part of Nepal and determine Minimum Inhibitory Concentration (MIC) of lichen extract.Methods: Everniastrum nepalense was collected from local Rai and Limbu community in a plastic bag from four hilly districts (Pachthar, Taplejung, Dhankuta and Bhojpur) of Eastern, NepaMoisture content in lichen samples were removed by air drying and grinded to powdery form. The methanolic extracts of lichens of different places were prepared by solvent extraction process using Soxhlet apparatus and tested against human pathogenic bacteria by disc diffusion method. Then, Minimum Inhibitory Concentration (MIC) of lichen extracts was determined using well diffusion method.Results: The lichens extract against the test bacterial isolates were performed by agar well diffusion method. Overall, it was observed that all these lichen extracts from Eastern Nepal had inhibitory effect on both gram-positive and gram-negative bacteria. Out of seven bacterial samples used, all bacterial samples were inhibited by the lichen extracts except Escherichia coli. The effect of lichen extract collected from Bhojpur district had maximum zone of inhibition against Staphylococcus aureus, Salmonella Typhi and Klebsiella spp were found to be 13 mm, 14 mm and 14 mm respectively. Similarly, zone of inhibition against Bacillus subtilis was found to be 17 mm from samples of Dhankuta, which was highest value than other 3 districts viz; Bhojpur, Taplejung and Pachthar District. Likewise, Pseudomonas aeruginosa showed highest inhibition value i.e. 18 mm on Pachthar sample whereas, Shigella showed 15 mm on Dhankuta sample. This study revealed that inhibitory capacity of edible lichen (Everniastrum nepalense) against test bacteria was not the same. It varied from place to place.Conclusion: This study has concluded that Everniastrum nepalensehas potential antibacterial property against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Salmonella spp, Shigella spp, Klebsiella spp and Pseudomonas aeruginosa except E. coli along with nutritional value and can be used as safe alternative and economic herbal medicine to treat infectious diseases.